Robotic Prostatectomy Has a Superior Outcome in Larger Prostates and PSA Density Is a Strong Predictor of Biochemical Recurrence. (15th December 2014) - Bishara, S.; Vasdev, N.; Lane, T.; Boustead, G.; Adshead, J.
Abstract : Objectives . The aims of this study were to compare the outcomes of robotic assisted laparoscopic prostatectomy (RALP) between patients who had larger (≥75 g) and smaller (<75 g) prostates and to evaluate the performance of PSA density (PSAD) in determining the oncological outcome of surgery. Methods and Materials . 344 patients who underwent RALP at a single institution were included in the study. Preoperative risk factors and postoperative, oncological outcomes, erectile function, and continence status were recorded prospectively. Results . During a mean follow-up of 20 months, biochemical recurrence PSA > 0.2 was observed in 15 patients (4.3%). Prostate size ≥75 g was associated with lower Gleason score on final pathology P = 0.004 and lower pathological stage P = 0.02 but an increased length of hospital stay P = 0.05 . PSAD on binary logistic regression independently predicted biochemical recurrence (BCR) when defined as postoperative PSA >0.1 P = 0.001 and PSA >0.2 P = 0.039 . In both instances PSA was no longer a significant independent predictor. Conclusions . RALP in large prostates (≥75 g, <150 g) is as safe as RALP in smaller prostates and is associated with a lower pathological grade and stage. Higher PSAD is independently associated with BCR and is superior to PSA as a predictor of BCR after RALP.